Fruit provision from Berberis microphylla shrubs as ecosystem service in Nothofagus forest of Tierra del Fuego - Bustamante, Gimena Noemi; Soler Esteban, Rosina Matilde; Blazina, Ana Paula; Arena, Miriam Elisabet (Heliyon)
Berry production is a non-wood product worldwide recognized by its nutritional value and taste, but the most studied species are non-native commercial plants in productive areas, leaving aside native berries. We propose that native berries (Berberis microphylla G.Forst) naturally growing in degradation forests areas could diversify livestock establishment production and complement traditional uses (e.g., livestock). The aims of this work were to 1) environmentally characterize (e.g., soil nutrient content and physical conditions, air conditions and photosynthetically active radiation) in three degraded Nothofagus antarctica Oerst. forest (due to past fires and livestock use) of Tierra del Fuego; and 2) evaluate berries production of B. microphylla in terms of quality production (e.g., fruit number and weigh per shrub) and in terms of quality (individual fruit weight, fruit pulp percentage, and soluble solids content) to assess provisioning ecosystem service of this native shrub in different degraded areas. Studied sites were defined as: 1) Severe soil degradation condition (SEV) (high frequency of horses, bulls and some native guanacos year round, severe soil erosion, and shorter herbaceous layer), 2) Moderate soil degradation condition (MOD) (cattle and guanaco year round, intermediate level of soil erosion and intermediate height of herbaceous layer), and 3) Slight soil degradation condition (SLI) (livestock only during winter, but high frequency of native guanacos, lower soil erosion and taller herbaceous layer). (SEV) had the highest air and soil temperature, least soils nutrients content, highest bulk density, the least soil water content and the poorest fruit production. (MOD) had the highest soil water content and nutrient-rich soils, while (SLI) had the highest relative air humidity and PAR. B. microphylla shrubs grow with similar morphology on the different soil degraded condition. The highest fruit production were at (SLI), however the (SEV) had the highest soluble solids. We conclude that calafate ...